ANALISIS KEUNTUNGAN KERAJINAN BAMBU TUTUL DI UD BETRIS KELURAHAN MERAS KECAMATAN BUNAKEN KOTA MANADO - Deisi ., Wongkar; Agnes Estephina Loho; Theodora M. Katiandagho (Sam Ratulangi University, 2018)
The purpose of this study was to analyze the profits of souvenir key chains, miniature of large traditional houses, miniature of small traditional houses and miniature flowers at UD Betris. The data used in this study are primary data and secondary data. Primary data is data obtained by interviewing with owners of UD Betris spotted bamboo handy handycrafts in Meras Village, Bunaken District, Manado City. Secondary data was obtained from the internet through Google Scholar in the form of scientific journal articles and books related to this research topic. The profits of this business are different according to the type of handycrafts. The highest profit was obtained from the sale of large miniature traditional houses, namely Rp. 1,609,425; followed by the advantages of small traditional miniature houses of Rp. 716,480; the profit obtained from miniature interest is Rp. 179,165; while the lowest profit from the souvenir key chain is Rp. 5,898.*lrr+eprm*